The Impact of L-Carnitine and Coenzyme Q10 as Protection Against Busulfan-Oxidative Stress in the Liver of Adult Rats - Abdelrazek, Areeg M.; Haredy, Shimaa A. (Natural Products Journal, The, 2020)
Background: Busulfan (Bu) is an anticancer drug with a variety of adverse effects for cancer patients. Oxidative stress has been considered as a common pathological mechanism and it has a key role in the initiation and progression of liver injury by Bu. Aim: The study aimed to evaluate the antioxidant impact of L-Carnitine and Coenzyme Q10 and their protective role against oxidative stress damage in liver tissues. Material and Methods: Thirty-six albino rats were divided equally into six groups. G1 (con), received I.P. injection of DMSO plus 1 ml of distilled water daily by oral gavages; G2 (Bu), received I.P. injection of Bu plus 1 ml of the distilled water daily; G3 (L-Car), received 1 ml of L-Car orally; G4 (Bu + L-Car) received I.P. injection of Bu plus 1 ml of L-Car, G5 (CoQ10) 1 ml of CoQ10 daily; and G6 (Bu + CoQ10) received I.P. injection of Bu plus 1 ml of CoQ10 daily. Results: The recent data showed that Bu induced significant (P<0.05) elevation in serum ALT, AST, liver GSSG, NO, MDA and 8-OHDG, while showing significant (P<0.05) decrease in liver GSH and ATP. On the other hand, L-Carnitine and Coenzyme Q10 ameliorated the negative effects prompted by Bu. Immunohistochemical expression of caspase-3 in liver tissues reported pathological alterations in Bu group while also showed significant recovery in L-Car more than CoQ10. Conclusion: L-Car, as well as CoQ10, can enhance the hepatotoxic effects of Bu by promoting energy production in oxidative phosphorylation process and by scavenging the free radicals.
Keywords: oxidative stress